The effect of Aerobic training on Klotho-FGF23 axis and arterial calcification in type 2 diabetic Postmenopausal women - Hamid Rajabi; mohammadreza Afkhamy ardakani; Pezhman Motamedi; Neda Khaledi (Shahid Beheshti University, 2020)
Purpose: Although exercise is one of the Medical aid strategies to reduce arterial stiffness in diabetic patients, but the mechanism remains unclear. The purpose of this study was to determine the effect of aerobic exercise on Klotho-fibroblast growth factor-23 (FGF23) axis and arterial calcification in type 2 diabetic Postmenopausal women. Methods: Twenty-four type-2 diabetic Postmenopausal women who were registered at the diabetes association of Shahrood, randomly assigned into two groups including exercise (n=12, 51±6 yrs, 31.9±5 kg/m2) and control (n=12, 52±5 yrs, 29.23.8 kg/m2). The aerobic training consisted of 45 to 60 minutes running with 45 to 70 percent of heart rate reserve, three sessions per week for 8 weeks. Before and after the experimental period, blood fasting samples were taken and the ELISA method was used to analyzed klotho and FGF23. Arterial stiffness analysis was also performed using VaSera-VS-2000. The data were analyzed using the statistical tests of Paired and Independent t-test (P0.05). But, that calcium levels in exercise group decreased significantly following the experimental period (P